2016
DOI: 10.3390/s16091514
|View full text |Cite
|
Sign up to set email alerts
|

Combined Dielectrophoresis and Impedance Systems for Bacteria Analysis in Microfluidic On-Chip Platforms

Abstract: Bacteria concentration and detection is time-consuming in regular microbiology procedures aimed to facilitate the detection and analysis of these cells at very low concentrations. Traditional methods are effective but often require several days to complete. This scenario results in low bioanalytical and diagnostic methodologies with associated increased costs and complexity. In recent years, the exploitation of the intrinsic electrical properties of cells has emerged as an appealing alternative approach for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 159 publications
0
28
0
Order By: Relevance
“…While the label-free characteristic of DEP manipulation has traditionally enabled sample preparation for detection of molecular nucleic-acid type biomarkers by enhancing capture efficiency and selectivity for impedance-based detection, current trends are directed towards the application of DEP within miniaturized point-of-care type microbial concentration 225,226 and sensing devices 227 . A prime example of this is the commercialization of the DEPIM technology by Panasonic Healthcare in the form of a microbial counter for dental applications.…”
Section: Challenges and Emerging Needsmentioning
confidence: 99%
“…While the label-free characteristic of DEP manipulation has traditionally enabled sample preparation for detection of molecular nucleic-acid type biomarkers by enhancing capture efficiency and selectivity for impedance-based detection, current trends are directed towards the application of DEP within miniaturized point-of-care type microbial concentration 225,226 and sensing devices 227 . A prime example of this is the commercialization of the DEPIM technology by Panasonic Healthcare in the form of a microbial counter for dental applications.…”
Section: Challenges and Emerging Needsmentioning
confidence: 99%
“…Changes in the dielectricity or conductivity, as for dead cells, membrane truncation or different cell phases, affect the electrical impedance and the dielectrophoretic migration, and thus can be detected [8][9][10][11]. Dielectrophresis is the migration of an electrically polarisable object in an inhomogeneous electric field.…”
Section: Introductionmentioning
confidence: 99%
“…EIS (electrical impedance spectroscopy) devices have been widely employed in biological studies, such as single cell analysis [1,2,3,4,5,6,7,8,9] and virus detection [10,11,12,13,14,15]. In particular, many studies have reported significant differences in electrical impedance between dissimilar cells or tissues from various organs [16,17,18,19,20,21,22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%